A Review of the Streets and Gates of Istanbul Grand Bazaar - Dilaveroglu, Inci; Pilehvarian, Nuran Kara (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2022)
In this article, which is aimed to mention the gates and streets that are indispensable parts of the spatial development of the Istanbul Grand Bazaar, it is aimed to draw attention to the actual elements that are the main beneficiaries of the closed identity of the Grand Bazaar by including location, material and measurement details as well as a general analysis from the past to the present. The Grand Bazaar has resisted various disasters such as fire and earthquakes for centuries and reached the present day with many renovations and changes. With the decision of the Conservation Regional Board, it has entered into a new and comprehensive restoration proces to respond to today's needs and to be freed from some illegal parts. After this restoration process, some settled changes will be included in the plan. In recent years, a preliminary project study was carried out by the district municipality in the region and various analyzes and reports were made in 2010 within this project. Although the Preliminary Project process was interrupted for a while due to legal reasons, as of the end of 2021, the renovation works are continuing rapidly. In this article, the analysis of the gates and covered streets that separates the Grand Bazaar from the commercial area it is in and that makes it a privileged structure, are mentioned. In addition, measurements and definitions that emerged as a result of on-site investigations and photographs taken before the last restoration are also included.
Keywords: Istanbul Grand Bazaar; Istanbul Grand Bazaar Monumental Gates; Istanbul Grand Bazaar Streets; Grand Bazaar Beyazit Gate; Grand Bazaar Nur-u Osmaniye Gate; Art